Brief Report: A Specialized Fitness Program for Individuals with Autism Spectrum Disorder Benefits Physical, Behavioral, and Emotional Outcomes - Jackson, S.L.J.; Abel, E.A.; Reimer, S.; McPartland, J.C. (Journal of Autism and Developmental Disorders, 2022)
Individuals with autism spectrum disorder (ASD) engage in less physical activity than typically-developing peers. This can result in serious negative consequences for individual well-being and may contribute to the physical, behavioral, and emotional challenges associated with ASD. This study explored the potential benefits of trainer-led, individualized, physical fitness sessions specialized for ASD. Eleven individuals (ages 7–24 years) with ASD were assessed at baseline and following 15 fitness sessions. Participants demonstrated improvements in core and lower-body strength and reductions in restricted and repetitive patterns of behavior, along with non-significant but marked reductions in issues with daytime sleepiness. Results suggest the merit of specialized fitness programs and emphasize the need for larger and more rigorous research studies on this topic. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Autism spectrum disorder; Exercise; Fitness; Physical health; Restricted and repetitive behaviors; Sleep behaviors; dept.aa; dept.adm; peer-reviewed

New England Town Meeting and the Cultivation of Deliberative Play - Townsend, Rebecca M.; Milburn, Trudy (American Behavioral Scientist, 2022)
Participants of New England town meeting must follow protocols to participate in this direct democratic process. Over the past 200 years, the protocols have been enacted and adapted by participants in small towns across the region. Within annual meetings, one can find small breaches that could be interpreted as playful acts. In this paper, we use the comic frame as a theoretical lens to interpret instances of such play within the rhetorical deliberation of one New England town meeting. We analyze two instances where speakers playfully use recognized parts of town meeting to achieve their rhetorical ends. We conclude with a discussion of the way play can help accomplish identification in public discourse.
Keywords: dept.aa; peer-reviewed